Human ABCE1 exhibits temperature‐dependent heterologous co‐functionality in S. cerevisiae. Issue 10 (19th July 2022) - Wada, Miki; Ito, Koichi
Abstract : ABCE1 protein (Rli1 in Saccharomyces cerevisiae ) is a unique ribosome recycling factor that is composed of an N‐terminal FeS cluster domain and two ATPase domains. Here, we report that heterologous expression of human ABCE1 in S. cerevisiae is unable to complement conditional knockout of ABCE1 (Rli1), at a typical experimental temperature of 30 °C. However, low but significant growth was observed at high temperature, 37 °C. Considering the close interaction of ABCE1 with translation factors and ribosomal components, the observed temperature‐dependent complementation may be attributed to heterologous co‐functionality of ABCE1 with S. cerevisiae factor(s), and might reflect functional upregulation of human ABCE1 at its functional temperature. Abstract : Heterologous expression of the human ortholog of ribosome recycling factor ABCE1 in Saccharomyces cerevisiae failed to complement conditional knockout of ABCE1 (Rli1) at 30 °C, but significant growth recovery was observed at high temperature (37 °C). Thermo‐dependent behavior of ABCE1 variants may aid in the elucidation of details of the ribosomal recycling pathway.